INVESTIGATING TEACHERS’ PROFESSIONAL COMPETENCE: A SYSTEMIC FUNCTIONAL LINGUISTIC ANALYSIS OF TEACHERS’ REPORT TEXTS - Sudarsono, Sudarsono M. I.; Yunitasari, Devi; Gunawan, Muhammad Handi (Indonesian Journal of Applied Linguistics, 2017)
This research aims at observing the teachers’ professional competence by investigating the report texts written by three English teachers in a junior high school in terms of their schematic structures and linguistic features. To achieve this aim, a qualitative case study design involving analysis of English teachers’ report texts and interviews with these English teachers was employed in this research. The results of this research showed that generally the three English teachers have demonstrated sufficient ability in applying appropriate schematic structures and linguistic features relevant to the criteria of a report text. However, the results of this research also indicate that some improvements in understanding and writing a report text, especially in terms of schematic structure, linguistic features, and theme progressions, are needed to enhance the teachers’ subject matter content knowledge about report text.